MANAJEMEN MATERIAL SUBSTRUCTURE DENGAN METODE MATERIAL REQUIREMENT PLANNING - Atmaja, Jajang; Riswandi, Riswandi; Natalia, Monika; Maifrianti, Riry; Hidayati, Fitri (Pusat Penelitian dan pengabdian kepada Masyarakat (P3M) Politeknik Negeri Padang, 2023)
Project management planning on sub structure area, very important to ensure efficient and effective construction projects. This research was purposes managing the sub structure material on precast pile and sloof using the material requirement planning (MRP) method in flat residence in West Sumatera. The scope research were the lot for lot (LFL) bar bending schedule and contingency plan (to minimize wasted material). The results of the analysis of study, the implementation of the MRP method (LFL technique) consists of cost of material planning on shop drawing, which was Rp.1,488,562,000,00; cost of material requirement planning by the lot for lot (LFL) technique was Rp.1,477,837,249,00; realization cost by combining the LFL technique and contingency plan is Rp.1,478,143,808,00. Calculation of the quantity and cost of reinforcing steel using the MRP method (LFL technique) by the bar bending schedule better than using the contingency method. Using bar bending schedule was more efficient, because it makes the remaining reinforcing steel after cutting was calculated properly.